Origin and evolution of the deep thermochemical structure beneath Eurasia - N. Flament (Nature Portfolio, 2017)
The Perm anomaly is found in the lower mantle beneath Eurasia, but how this structure formed has remained unclear. Here, the authors show that the anomaly has been mobile since it formed in isolation within a closed subduction network and propose that the anomaly is linked to the Emeishan volcanics.